2016
DOI: 10.17679/iuefd.17247323
|View full text |Cite
|
Sign up to set email alerts
|

Pedagojik Formasyon Programının Biyoloji, Fizik ve Kimya Öğretmen Adaylarının Öğretmenlik İmajlarına Etkisi

Abstract: Abstract:The purpose of this study is to examine the images of 73 pre-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 9 publications
0
1
0
3
Order By: Relevance
“…Similarly, Üner et al (2012) concluded in their study with pre-service chemistry teachers that pre-service chemistry teachers have both student-centered and teacher-centered images, and their teaching style is conceptual teaching style. In addition, in a study, it was concluded that the teaching images of pre-service chemistry teachers who received pedagogical formation education were both student-centered and teacher-centered, and their teaching styles were conceptual teaching styles (Üner & Akkuş, 2016). This situation can be interpreted as the education of pre-service teachers effecting the formation of their self-image and teaching styles.…”
Section: Results Discussion and Recommendationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, Üner et al (2012) concluded in their study with pre-service chemistry teachers that pre-service chemistry teachers have both student-centered and teacher-centered images, and their teaching style is conceptual teaching style. In addition, in a study, it was concluded that the teaching images of pre-service chemistry teachers who received pedagogical formation education were both student-centered and teacher-centered, and their teaching styles were conceptual teaching styles (Üner & Akkuş, 2016). This situation can be interpreted as the education of pre-service teachers effecting the formation of their self-image and teaching styles.…”
Section: Results Discussion and Recommendationsmentioning
confidence: 99%
“…(2012)'ın kimya öğretmen adayları ile yaptıkları çalışmada kimya öğretmen adaylarının hem öğrenci hem öğretmen merkezli imajlara sahip oldukları, öğretim stillerinin ise kavramsal öğretim stili olduğu sonucuna ulaşmışlardır. Ayrıca yapılan bir araştırmada, pedagojik formasyon eğitimi alan kimya öğretmen adaylarının kendilerine yönelik öğretmenlik imajlarının hem öğrenci hem öğretmen merkezli ve öğretim stillerinin ise kavramsal öğretim stili oldukları sonucuna ulaşılmışlardır (Üner & Akkuş, 2016). Alanyazında öğretmen merkezli imajlara sahip araştırma sonuçlarına da ulaşılmıştır.…”
Section: Veri Toplama Araçları Ve Verilerin Analiziunclassified
See 1 more Smart Citation
“…2010 yılından itibaren sayıca artan pedagojik formasyon eğitimi sertifika programları hakkındaki araştırmalarda da bu programlara olan yoğun ilginin nedenlerinin dolaylı olarak sorgulandığı görülmektedir. Bu araştırmalarda öncelikle öğretmenlik mesleği ile ilgili motivasyon (Altınkurt, Yılmaz ve Erol, 2014;Nayır ve Taneri, 2013;Polat, 2014); görüş (Aykaç, Bilgin ve Toraman, 2015;Çiçek Sağlam, 2015;Sever, Aktaş, Şahin ve Tunca, 2015), algı ve tutum (Bal, 2017;Bağçeci, Yıldırım, Kara ve Keskinpala, 2015;Demirtaş ve Aksoy, 2016;Dikmenli ve Çifçi, 2015;Eraslan ve Çakıcı, 2012;Gül ve Erkol, 2015;İlğan, Sevinç ve Arı, 2013;Kartal ve Afacan, 2012;Nartgün ve Gökçer, 2014;Özdemir ve Erol, 2015;Özkan, 2012;Üner ve Akkuş, 2016), özyeterlik algıları (Bulut ve Oral, 2011;Çocuk, Yokuş ve Tanrıseven, 2015;İpek ve Demirel, 2016;Süral ve Sarıtaş, 2015;Yazıcı ve Kalkavan, 2016), öğrenme stilleri (Güneş ve Gökçek, 2012); ve sosyal yetkinlik düzeyleri (Türkçapar, 2016) gibi konular incelenmiştir. Araştırmalar arasında pedagojik formasyon sertifika programı ile eğitim fakültesi öğrencilerinin öğretmenlik mesleğine yönelik tutum, duyarlılık, özyeterlilik inançlarının ve mesleki kimliklerinin karşılaştırıldığı çalışmalar da (Dede ve Akkoç, 2016;İncik ve Akay, 2015;Polat, 2013;Uygun, 2016) bulunmaktadır.…”
Section: Introductionunclassified